2005
DOI: 10.1105/tpc.105.034397
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids Stimulate Plant Tropisms through Modulation of Polar Auxin Transport in Brassica and Arabidopsis

Abstract: Brassinosteroids (BRs) are important plant growth regulators in multiple developmental processes. Previous studies have indicated that BR treatment enhanced auxin-related responses, but the underlying mechanisms remain unknown. Using 14 C-labeled indole-3-acetic acid and Arabidopsis thaliana plants harboring an auxin-responsive reporter construct, we show that the BR brassinolide (BL) stimulates polar auxin transport capacities and modifies the distribution of endogenous auxin. In plants treated with BL or def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
199
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(208 citation statements)
references
References 36 publications
9
199
0
Order By: Relevance
“…We also found that treatment with 10 nM BL did not significantly affect gravitropism of etiolated hypocotyls under our experimental conditions (data not shown). Li et al (2005) also found that BR promotes polar auxin transport through gene expression of PIN-FORMED (PIN) family proteins in agreement with a previous observation by Bao et al (2004). This seems important because it suggests that BR deficiency caused by dwf4 or Brz treatment may lead to reduction of polar auxin transport.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also found that treatment with 10 nM BL did not significantly affect gravitropism of etiolated hypocotyls under our experimental conditions (data not shown). Li et al (2005) also found that BR promotes polar auxin transport through gene expression of PIN-FORMED (PIN) family proteins in agreement with a previous observation by Bao et al (2004). This seems important because it suggests that BR deficiency caused by dwf4 or Brz treatment may lead to reduction of polar auxin transport.…”
Section: Discussionsupporting
confidence: 81%
“…A synergistic positive interaction between BR and auxin was reported for gravitropism of partially deetiolated bean (Phaseolus vulgaris) hypocotyl sections (Meudt, 1987) and dark-grown maize (Zea mays) primary roots (Kim et al, 2000). Recently, Li et al (2005) have also shown promotive effects of BR on root and hypocotyl gravitropism in Arabidopsis. They observed gravitropic curvature of roots and hypocotyls of dark-grown seedlings that were simultaneously irradiated with unilateral white light from above.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses have revealed the critical roles of the influx carrier AUX1 and efflux carrier PIN proteins in gravity response. Mutation in AUX1 abolishes root gravitropic curvature [36]; similarly, pin2 seedlings are agravitropic, whereas PIN2 overexpression results in an enhanced tropistic response [37,38]. The lateral relocation of PIN3 in response to gravity redirects the auxin flux and mediates tropism in Arabidopsis [39].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is unknown whether this protein is also required for phototropism [27]. Growth responses such as phototropism require auxin and brassinosteroids [28][29][30][31] while there is no evidence suggesting that these hormones are involved in the control of chloroplast movements. For chloroplast movement responses the nucleus is not even required [20].…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 99%